The Process of Counselling: A Spiral Model - Daniluk, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2011)
Students must often attempt to understand the dynamic process of counselling, within a framework of models which largely represent it as a linear, sequential process. The "spiral model" being proposed represents a shift from a mechanistic, linear conception of counselling to one which places emphasis on the dynamic, fluid nature of the interaction between client and counsellor. This model may assist practitioners in conceptualizing counselling from a more holistic perspective. It also recognizes and validates the interdependence of client and counsellor in providing direction and generating movement within the counselling process.